Assessing the robustness of composite indicators: The case of the Global Innovation Index - Khatab Alqararah (Journal of Innovation and Entrepreneurship, 2023)
This research paper introduces a methodology to assess the robustness of the Global Innovation Index (GII), by comparing the rankings provided in it with those achieved using alternative data-driven methodologies such as data envelopment analysis (DEA) and principal component analysis (PCA). With it, the paper aims to reduce the level of subjectivity in the construction of composite indicators regarding weight generation and indicator aggregation. The paper relies on PCA as a weighting-aggregation scheme to reproduce the 21 sub-pillars of the GII before the application of DEA to calculate the relative efficiency score for every country. By using the PCA-DEA model, a final ranking is produced for all countries. The random forests (RF) classification is used examine the robustness of the new rank. The comparison between the new rank and that of the GII suggests that the countries positioned at the top or the bottom of the GII rank are less sensitive toward the modification than those in the middle of the GII, the rank of which is not robust against the modification of the construction method. The PCA-DEA model introduced in this paper provides policymakers with an effective tool to monitor the performance of national innovation policies from the perspective of their relative efficiency. Ultimately, the contribution made in this paper could be instrumental to enhance the effectiveness and the efficiency of the practice of innovation management at the national level.
Keywords: 650; Innovation performance; Composite indicators; Data envelopment analysis; Global Innovation Index; Principal component analysis; Random forests